Real exchange rate in an inter-temporal n-country-model with incomplete markets - Benoît Mercereau (European Central Bank (ECB), 2003)
We develop an N-country model with stock markets in which closed-form solutions for the real exchange rate is derived. Our model allows for a given number of risky-assets, which form an incomplete market. Risky asset prices and allocations of risky assets among countries are determined endogenously. The risk-free rate is exogenous, so our model is an intermediate step toward a full general equilibrium. To work in such a framework allows an analysis of how fundamental parameters, such as the variance and covariance of the risky assets or demographic variables, affect the real exchange rate. We contrast the predictions of the model to the Balassa-Samuelson effect. We also suggest a new transmission channel of the real exchange rate for parameters such as income on net foreign assets, risk-aversion and risk-hedging opportunities.
Keywords: F30; F31; F32; F41; 330